Efektivitas Penerapan Asas Itikad Baik pada Transaksi Jual Beli Hasil Bumi di Desa Sidetapa Kabupaten Buleleng - Putu Linda Juli Swandewi; I Nyoman Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
The village of Sidetapa uses an oral agreement system in selling its produce which is only based on good faith. The factor that causes people to still use oral agreements is the low level of education and habits so that it can cause problems that will occur in the future due to the absence of a written agreement. The purposes of this study are to determine the application of the principle of good faith in the sale and purchase of agricultural products in Sidetapa Village, Buleleng Regency as well as legal liability for default in the sale and purchase transactions of agricultural products that are not in good faith. The research method in this is an empirical research method with a sociological approach. The data sources used are primary and secondary legal sources. Data collection techniques were carried out by observation, interviews and literature study which were then presented in qualitative form. The results of the study reveal that every agreement must be based on good faith as in the sale and purchase agreement of agricultural products in Sidetapa Village. This agreement system is effective because it is quite simple and easy to implement. This verbal agreement does not rule out the possibility that someone does not default, if there is a default in buying and selling in the village of Sidetapa, the settlement is in a familial way.